Right to Pray and Gender Debate in India - Khurana, Neeta Avtar (Advances in Social Sciences Research Journal, 2017)
The article apprises about the historical and contemporary debate on Right to equality from a Gendered perspective in India. The recent and ongoing turmoil surrounding right to pray and its link with the larger question of women’s emanicipation as the central theme of the article. The paper notes that the clamour for Temple Entry is a refreshing trend in the Women’s movement in India as it replaces the State with Civil Society as the arbiter of Change. An attempt has been made in the paper to offer a historical survey of the women’s movement in India and place competing narratives of the Gender debate. Religion, Female Bpdy, and Women’s movement in India are three key interfaces encompassing this paper.